2016
DOI: 10.7763/ijesd.2016.v7.732
|View full text |Cite
|
Sign up to set email alerts
|

Groundwater Quality Investigation Using Multivariate Analysis — Case Study: Western Nile Delta Aquifer, Egypt

Abstract: Factor analysis is applied on the 19 parameters to investigate the origin of the water pollution sources. Multivariate analysis showed the existence of up to four significant factors which account for 77.0 % of the total variance of hydrochemistry data. The first two factors can be initially assigned to mineralization, mining and salinity due to saltwater intrusion whereas the others originate as a result of industrial wastes, domestic wastes and wastes from agriculture activities. This work will provide polic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…A study conducted at the same area, showed high concentration of trace elements including iron and manganese (36) . Other study showed that water was generally of good quality, at most parts of the studied area (45) . The concentration of chromium, cadmium, lead and zinc were all within the permissible limits of drinking water quality (30) .…”
Section: Groundwater Contaminantsmentioning
confidence: 78%
“…A study conducted at the same area, showed high concentration of trace elements including iron and manganese (36) . Other study showed that water was generally of good quality, at most parts of the studied area (45) . The concentration of chromium, cadmium, lead and zinc were all within the permissible limits of drinking water quality (30) .…”
Section: Groundwater Contaminantsmentioning
confidence: 78%
“…The spatial analysis extension of GIS enables the interpolation of observed groundwater quality parameters to create a concentration map of water quality parameters for the entire area. Armanuos et al (2016) utilized GIS along with multivariate statistical analysis to investigate groundwater suitability for drinking and irrigation in the Western Nile Delta of Egypt. El-Zeiny and Elbeih (2019) estimated the WQI to evaluate groundwater quality in Dakhla Oasis, Egypt, for drinking purposes according to Egyptian and WHO standards.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies were carried out on groundwater quality evaluation and hydrochemical characterization (Brindha et al 2014;Sajil Kumar et al 2014;Wu et al 2014Wu et al , 2015Bouzourra et al 2015;Vetrimurugan and Elango 2015;Li et al 2016). In addition, many researchers in Egypt have focused on groundwater resources in terms of quality (Masoud 2014;Armanuos et al 2016;Negm and Armanuos 2017;El-Rawy et al 2019;Salem et al 2019;Ding et al 2020;Hegazy et al 2020;Mansour 2020;El-Kholy et al 2022).…”
Section: Introductionmentioning
confidence: 99%